2004
DOI: 10.1093/occmed/kqh090
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of self-reported occupational injuries in seafaring--an international study

Abstract: There was no evidence that long working hours alone resulted in higher injury rates. Low self-perceived health, lack of use of personal protection and lack of occupational safety on board were significantly related to an increase in the injury risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
27
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 21 publications
7
27
0
Order By: Relevance
“…Even so, seafarers have higher hospitalization and mortality rates than agematched peers, particularly for traumatic causes [5,6]. In fact, as many as 9% of seafarers report being injured during a single tour of duty, with nearly half of them unable to work for at least 1 day as a result [7]. Three other international entities have published data regarding a similar service.…”
Section: Discussionmentioning
confidence: 99%
“…Even so, seafarers have higher hospitalization and mortality rates than agematched peers, particularly for traumatic causes [5,6]. In fact, as many as 9% of seafarers report being injured during a single tour of duty, with nearly half of them unable to work for at least 1 day as a result [7]. Three other international entities have published data regarding a similar service.…”
Section: Discussionmentioning
confidence: 99%
“…Seafarer jobs were classified by the worksite (deck, engine room, and galley) as well as rank (officers or ratings), to allow comparison with previous seafarer studies [12,14,15]. The injured body part and illness types as listed in the database were classified into more general categories by the authors.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…Severe environmental conditions on board, hazardous activities and lack of occupational safety on board increase the incidence of shipboard injuries. An international study including 11 countries revealed an incidence RR (IRR) of 37.6 per 100 000 days for cargo ships and tankers 16. The IRR for non-officers compared with officers was 1.57 (95% CI 1.14 to 2.15), and for seafarers <35 years compared with ≥35 years of age, the IRR was 2.11 (95% CI 1.57 to 2.86).…”
Section: Hazards Of the Job And The Workplacementioning
confidence: 99%